A bidentate Polycomb Repressive-Deubiquitinase complex is required for efficient activity on nucleosomes - Martina Foglizzo (Nature Portfolio, 2018)
The Polycomb Repressive-Deubiquitinase (PR-DUB) complex is responsible for the removal of the ubiquitin epigenetic modification from Histone 2A. Here the authors describe the structure of the Drosophila PR-DUB complex, providing new insight into its regulation and how cancer-associated mutations disrupt PR-DUB activity.